2012
DOI: 10.1017/s1743921312017176
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Quasars and Stars by Supervised and Unsupervised Methods

Abstract: Targeting quasar candidates is always an important task for large spectroscopic sky survey projects. Astronomers never give up thinking out effective approaches to separate quasars from stars. The previous methods on this issue almost belong to supervised methods or color-color cut. In this work, we compare the performance of a supervised method -Support Vector Machine (SVM)-with that of an unsupervised method one-class SVM. The performance of SVM is better than that of one-class SVM. But one-class SVM is an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…With modern telescopes recording an increasingly large amount of astronomical data, the usage of machine learning models in the task of classification has become more and more significant and prevalent because of their accuracy and speed (Clarke et al, 2020). While reviews of previous studies with similar objectives of classifications found both supervised and unsupervised machine learning models to be capable of great performance with accuracy and other metrics measured at over 90%, the supervised models had generally higher accuracies in classification, and unsupervised models were shown to be more effective at detecting unknown objects (Viquar et al, 2018;Zhang et al, 2013). With supervised ML models, the classification models of random forest and support vector model (SVM) were used, along with decision tree and logistic regression, to either solely identify and separate quasars from other objects or to classify all three of stars galaxies, and quasars (Carrasco et al, 2015).…”
Section: Significance and Literature Reviewmentioning
confidence: 99%
“…With modern telescopes recording an increasingly large amount of astronomical data, the usage of machine learning models in the task of classification has become more and more significant and prevalent because of their accuracy and speed (Clarke et al, 2020). While reviews of previous studies with similar objectives of classifications found both supervised and unsupervised machine learning models to be capable of great performance with accuracy and other metrics measured at over 90%, the supervised models had generally higher accuracies in classification, and unsupervised models were shown to be more effective at detecting unknown objects (Viquar et al, 2018;Zhang et al, 2013). With supervised ML models, the classification models of random forest and support vector model (SVM) were used, along with decision tree and logistic regression, to either solely identify and separate quasars from other objects or to classify all three of stars galaxies, and quasars (Carrasco et al, 2015).…”
Section: Significance and Literature Reviewmentioning
confidence: 99%
“…There is a significant increase in research works related to stellar spectra detection and classification. Many researchers focused on star-quasar (Zhang et al 2011;Jin et al 2019;Zhang et al 2009Zhang et al , 2013Viquar et al 2018), galaxy-quasar (Bailer-Jones et al 2019 or star-galaxy Philip et al (2002) binary classification. Others (López et al 2010, Becker et al 2020) focused on multi-class classification of stars, galaxies and quasars Cabanac et al (2002); Acharya et al (2018).…”
Section: Previous Workmentioning
confidence: 99%
“…Many authors used classical machine learning algorithms such as support vector machines (SVM) or k-nearest neighbors (kNN) (Zhang et al 2011(Zhang et al , 2009(Zhang et al , 2013Tu et al 2015,[12,15], Jin et al 2019;Viquar et al 2018). Others adopted deep learning techniques (Becker et al 2020, 11) or developed their own novel solutions (Viquar et al 2018).…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations